Pengaruh Pengalaman Kerja, Kompetensi, dan Independensi Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi (Pada Kantor Akuntan Publik Provinsi Bali) - Ni Made Rara Suhitha; I Made Wianto Putra; I. B. Made Putra Manuaba (Jurnal Riset Akuntansi Warmadewa, 2022)
The results of this study show that (1) Work Experience has no positive and significant effect on audit quality at public accounting firms in Bali province. This is indicated by the results of the t-test explained that the significance level of 0.460> 0.05 which means that the Work Experience variable has no significant effect on the Quality of Audits at the Public Accounting Firm of Bali Province. (2) Competency Variables have a significant effect on audit quality. This is indicated by the results of the test-t explained that the significance level> is 0.039< 0.05, which means that the Competency variable has a significant effect on audit quality. (3) The independence variable has no significant effect on audit quality. This is indicated by the result of the test-t has a Beta value of 0.258 and a Sig value. 0.013, which means that auditor ethics moderates the effect of work experience on audit quality. (5) Auditor Ethics moderates the effect of Competence on Audit Quality at Public Accounting Firms of Bali Province. Beta value of 0.275 and Sig value. 0.011, which means that auditor ethics moderates the effect of competence on audit quality. (6) Auditor Ethics moderates the effect of Independence of Audit Quality in Public Accounting Firms of Bali Province. This is indicated by the result of the test-t has a Beta value of 0.249 and a Sig value. 0.022, which means that Auditor Ethics moderates the effect of Work Experience on Audit Quality.